P3 Differences between attitudes to HIV testing and HIV testing practice among hospital doctors. (23rd May 2012) - Taylor, R; Pammi, M; Venkatesan, P
Abstract : Background: The BHIVA/BASHH/BIS UK Guidelines for HIV Testing (2008) state that all acute medical admissions in high prevalence areas, and all patients with specific clinical indicator conditions (CICs) should be offered an HIV test. Aims: As our Acute Trust serves a Primary Care Trust with a high prevalence of HIV (2.35/1000), we aimed to explore the attitudes towards HIV testing among hospital practitioners, the actual practice of testing and whether this reflected physician's stated attitudes. Methods: An electronic survey was circulated to all doctors within the Trust. The survey explored respondents' experience, awareness, knowledge, training requirements and willingness to expand HIV testing. A separate paper-based questionnaire was sent to Clinical Leads in selected specialties to explore local testing policy. Results: 214 responses were received from the online-survey. 76% had experience in testing, 73% felt they had necessary skills and 82% felt comfortable offering an HIV test. However, 45% had some concerns that their knowledge of HIV would be insufficient to answer patient questions. 99% favoured expanding HIV testing. The specialty survey revealed that only 20% of specialties had any departmental policy on testing. For one-third of AIDS-defining CICs only selective testing was offered. 7% of CICs would never prompt a test, 7% would always prompt a test and 86% would prompt testing only in selective circumstances. Conclusions: Most doctors agreed with the importance of expanding HIV testing and felt they had the requisite skills. However, despite this, the practice of HIV testing varied and did not meet with UK Guidelines. If efforts to expand HIV testing in our Trust are to succeed, we need to continue to support and engage clinicians, to initially focus on facilitating strong departmental policies for AIDS-defining conditions prior to widening scope to include other testing strategies.